Determining and assessing the significant barriers of transferring unfinished construction projects from the public sector to the private sector in Iran - Sarvari, Hadi (Emerald Group Holdings Ltd., 2021)
Purpose: The government sometimes lacks sufficient financial, management and technical capabilities to deliver construction projects. As a result, it has recognized the need to introduce private sector capital and expertise to complete unfinished construction projects. This outsourcing paradigm is known as a public-private partnership, a form of privatization. This study aims to identify the barriers associated with the transfer of unfinished construction projects to the private sector in Iran and grouped them into areas that were ranked to shed light on where the risk lies. Design/methodology/approach: After a thorough and comprehensive literature review, a questionnaire was developed and distributed to 67 experts in the public and private sectors in Iran. The survey included 37 barriers grouped into seven areas and measured on a five-point Likert scale. Face validity, content validity and structural validity of the collected data were confirmed. The reliability of the questionnaire was also tested and validated using Cronbach’s alpha coefficient. Findings: The survey findings indicated that private company laws, national constitution, government policies, lack of sufficient regulations, one-sided regulations and lack of balance, the regulations of other organizations and taxation laws were perceived as the major barriers to the transfer of unfinished public sector construction projects to the private sector in Iran. The ranking of the seven areas produced the following top three ranked barriers areas: taxation laws, government policies and one-sided regulations and lack of balance of importance. Originality/value: The elicitation of this study can be useful to both private and public sectors for the development of infrastructure construction projects.